CRISISS99 - MỘT PHƯƠNG PHÁP ĐÁNH GIÁ ĐỘ NGUY HIỂM CỦA ĐỘNG ĐẤT MỚI - Thành, Trần Thị Mỹ; Hùng, Phạm Quang; Dương, Nguyễn Ánh (Vietnam Journal of Earth Sciences, 2005)
CRISISS99 compute the seismic hazard using a probability model to consider the occurrence and distribution of earthquake, and uses the seismicity in sources to estimate with attenuation laws the decay with distance of the ground motion from the source to a site. This paper introduces the program CRISISS99 and its apply for seismic hazard assessment in Northern part of Vietnam. The PGA maps for 200, 475 and 1000 years of the Northern part of Vietnam are presented